Assessing the Accuracy of a Computer-Aided Detection System for Suspected Malignant Breast Lesions Using Magnetic Resonance Imaging - Naderi Beni, Zahra; Farghadani, Maryam; Riahinejad, Maryam; Adibi, Atoosa; Lashkarblock, Maryam (Reports of Radiotherapy and Oncology, 2024)
Background: Mammograms often reveal breast microcalcifications, necessitating invasive procedures to ascertain whether they are cancerous or benign. Objectives: Although many microcalcifications are linked to noncancerous conditions, this study sought to investigate the efficacy of a computer-aided detection (CAD) system using breast MRI in distinguishing between benign and malignant breast anomalies. Methods: This cross-sectional study included forty patients with mammographically suspicious microcalcifications who underwent stereotactically-guided biopsies at our institution over two years. Prior to the biopsy, these patients received a breast MRI within eight weeks. Surgical interventions were carried out for cases identified as malignant or of uncertain malignant potential. The study aimed to determine diagnostic benchmarks by comparing the breast imaging reporting and database system (BI-RADS) category assignments from initial mammography screenings and breast MRI reports to the pathology findings. Results: Histopathology reports showed that of the total cases, 23 were benign, and 17 were malignant. Breast MRI exhibited a sensitivity of 88.8%, specificity of 54.5%, a positive predictive value of 58.5%, and a negative predictive value of 94.1%. Further analysis using CAD demonstrated sensitivity, specificity, positive predictive value, and negative predictive value of 100%, 50.0%, 59.0%, and 100%, respectively. Conclusions: Utilizing breast MRI with the support of CAD, radiologists could significantly enhance their capability to differentiate between benign and malignant mammographic microcalcifications. This innovative diagnostic approach has the potential to decrease the necessity for unnecessary breast biopsies.